Nevus sebaceus of Jadassohn associated with macro optic discs and conjunctival choristoma - Kruse, Friedrich E.; Rohrschneider, Klaus; Burk, Reinhard; Völcker, Hans Eberhard (Archives of ophthalmology, 1998)
Following Jadassohn's report in 1895, congenital ocular findings such as epibulbar choristomas (lipodermoids, aberrant lacrimal glands, cartilage), corneal pannus, colobomas (eyelid, iris, retina or choroid, optic nerve), and optic nerve hypoplasia but not macro optic discs have been described in combination with a facial nevus sebaceus.
Gesehen am 08.07.2024